A Brief History of Knowledge for Social Science Researchers: Before Method, 1st edition - Court, Deborah (Routledge, 2020)
A Brief History of Knowledge for Social Science Researchers outlines a history of knowledge from Ancient Greece to present day, in Europe and the Western world. This outline provides the basis for understanding where various research methods originate, and their epistemological, historical, political and social roots.